Standing Out from the Crowd via CSR Engagement: Evidence from Non-Fundamental-Driven Price Pressure - Gao, Lei; He, Jie (Jack); Wu, Juan (Julie) (Journal of Financial and Quantitative Analysis, 2024)
Abstract We test the signaling view of corporate social responsibility (CSR) engagement using two complementary quasi-natural experiments that impose exogenous negative pressure on stock prices. Firms under such adverse price pressure increase CSR activities compared to otherwise similar firms. This effect concentrates among firms with stronger signaling incentives, namely, those facing greater information asymmetry, more product market competition, higher shareholder litigation risk, and higher stock price crash risk. Firms under the exogenous negative price pressure mainly improve CSR strengths, including costly environmental investments. We also find that CSR engagement attracts socially responsible investors and lowers the cost of capital for signaling firms.